Natural product in plant pest management - Dubey, N. K. (CABI, 2011)
Overzealous and indiscriminate use of many synthetic pesticides during recent decades in the control of plant pests has resulted in a number of environmental and toxicological problems. Reducing the release of synthetic chemicals into the environment requires that alternative sources of chemicals are developed that can be used safely in the management of plant pests. Botanical antimicrobials derived from plants are currently recognised as biodegradable, systemic, eco-friendly and non-toxic to mammals and are thus considered safe. Their modes of action against pests are diverse. Natural compoun